Music and gender in the sub-arctic Algonkian area - Diamond, Beverley (Women in North American I[*****] Music: Six Essays, 1989)

Le plain-chant chez les Amérindiens - Dubois, Paul-André (Grégoriana, 1989)
Keywords: Pas de lien web

The Morphology and Phonology of Katajjait (Inuit Throat Games) - Bagemihl, Bruce (Canadian Journal of Linguistics/Revue canadienne de linguistique, 1988)
A linguistic theory can be considered to have explanatory force if it may be extended to a body of facts considerably beyond the domain for which it was originally conceived. In general, the further the new domain is from the original, the greater the support that accrues to that theory. In this paper, a number of developments within current morphological and phonological theory will be utilized in the analysis of an extraordinary form of vocal behaviour, the katajjait (sg. katajjaq) or throat games of the Canadian Inuit. The result will be a revealing account of the structures of these katajjait, as well as a remarkable confirmation of principles of linguistic theory from a domain which has been hitherto unreported in the linguistic literature.

The Transmission of Algonkian Indian Hymns: Between Orality and Literacy - Cavanagh, Diamond (Musical Canada: Words and Music Honouring Helmut Kallmann, 1988)

Sémiologie des jeux vocaux Inuit - Nattiez, Jean-Jacques (Semiotica, 1987)
Keywords: Pas de lien web

Hymn Anomalies in Traditional Cree Song - Whidden, Lynn (Recherches amérindiennes au Québec, 1987)

An Ethnomusicological Study of the Traditional Songs of the Chisasibi Cree - Whidden, Lynn (Université de Montréal, 1986)

Une approche sémiologique du powwow contemporain canadien - Blundell, Valda (Recherches amérindiennes au Québec, 1985)

Les mythes et la musique naskapis - Cavanagh, Diamond (Recherches amérindiennes au Québec, 1985)

Le disque de musique amérindienne, IV. Nouveaux disques et cassettes de musique inuit - Nattiez, Jean-Jacques (Recherches amérindiennes au Québec, 1985)

Transformations musicales et culturelles chez les Cris de l’Est - Preston, Richard J. (Recherches amérindiennes au Québec, 1985)

Les hymnes, une anomalie parmi les chants traditionnels des Cris du Nord - Whidden, Lynn (Recherches amérindiennes au Québec, 1985)

Un projet d'éducation musicale à Wemindji, Québec - Whidden, Lynn (Recherches amérindiennes au Québec, 1985)

Musique inuit au Québec arctique : contribution à une méthode d'analyse en anthropologie de la musique - Montpetit, Carmen; Veillet, Céline (Les Cahiers de l'ARMuQ, 1984)

Some Aspects of Inuit Vocal Games - Nattiez, Jean-Jacques (Ethnomusicology, 1983)

The Rekkukara of the Ainu (Japan) and the Katajjaq of the Inuit (Canada): A Comparison - Nattiez, Jean-Jacques (The World of Music, 1983)

Traditional Cree Song and the Problem of Creativity in Music - Whidden, Lynn (Actes du quatorzième congrès des algonquinistes, 1983)

Comparisons within a Culture: The Example of the Katajjaq of the Inuit - Nattiez, Jean-Jacques (Cross-Cultural Perspectives on Music, 1982)

Le disque de musique amérindienne, III. La musique indienne sur disque : cent ans d’ethnomusicologie - Nattiez, Jean-Jacques (Recherches amérindiennes au Québec, 1981)

An Introduction to the Music of the Malecite Indians - Baskin, Suzan Ruth (Université Carleton, 1980)

Pour l'adéquation de la transcription en ethnomusicologie : l'exemple du katajjaq - Berthiaume-Zavada, Claudette (Canadian University Music Review, 1980)
Keywords: Music

Le disque de musique amérindienne, II. Introduction à l’écoute des disques de musique inuit - Nattiez, Jean-Jacques (Recherches amérindiennes au Québec, 1980)

The Fiddlers of James Bay - Rodgers, Bob (Office national du film du Canada, 1980)
This short documentary traces the history of the fiddle’s arrival in Canada 300 years ago via Scottish traders from Orkney Island. The Cree population of what is now Northern Québec adopted the instrument, and many contemporary Cree residents are master fiddlers. In this film, two Cree fiddlers travel to the Orkney Islands, the birthplace of the music they learned from their fathers and grandfathers. The film captures the warmth and good will of this reunion.